2019
DOI: 10.1029/2019jd030576
|View full text |Cite
|
Sign up to set email alerts
|

Simulating a Mesoscale Convective System Using WRF With a New Spectral Bin Microphysics: 1: Hail vs Graupel

Abstract: A modified Fast Spectral Bin Microphysics scheme (FSBM‐2) embedded into the Weather Research and Forecasting (WRF) model is used to simulate a mesoscale deep convective system observed during the Midlatitude Continental Convective Clouds Experiment (MC3E). FSBM‐2 uses modified source codes as compared to the current FSBM (FSBM‐1). In contrast to FSBM‐1, FSBM‐2 can simulate hail of several centimeters in diameter and includes additional processes such as spontaneous breakup of raindrops and aerosol regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 117 publications
0
26
0
Order By: Relevance
“…Lynn et al (2015), Khain et al (2016), Shpund, Khain, and Rosenfield (2019), and Shpund, Khain, Lynn et al (2019) describe in detail the SBM in WRF. The main specific features of the scheme are (a) all microphysical processes are described using the basic microphysical equations without parameterization, and (b) the scheme solves the equation for particle size distributions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lynn et al (2015), Khain et al (2016), Shpund, Khain, and Rosenfield (2019), and Shpund, Khain, Lynn et al (2019) describe in detail the SBM in WRF. The main specific features of the scheme are (a) all microphysical processes are described using the basic microphysical equations without parameterization, and (b) the scheme solves the equation for particle size distributions.…”
Section: Methodsmentioning
confidence: 99%
“…The model output frequency was every 15 min, and each simulation duration was for 66 h. Two days were allowed for model spin-up of the background aerosol, dust, and urban aerosol fields. , Khain et al (2016), Shpund, Khain, and Rosenfield (2019), and Shpund, Khain, Lynn et al (2019) describe in detail the SBM in WRF. The main specific features of the scheme are (a) all microphysical processes are described using the basic microphysical equations without parameterization, and (b) the scheme solves the equation for particle size distributions.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Several important differences between these models are highlighted here, with additional details presented in appendix A. First, six of the models utilized two-moment (2M) bulk microphysical parameterizations with varying levels of sophistication, whereas WRF-SBM used a spectral bin microphysics scheme with recent updates as detailed in Shpund et al (2019). Three models either prognose or diagnose supersaturation (RAMS, NU-WRF, WRF-SBM), while the other four models utilize saturation adjustment-a model process in which any liquid supersaturation that develops at a model grid point is completely eliminated at each time step via condensation onto already formed hydrometeors.…”
Section: Modelsmentioning
confidence: 99%
“…Lynn et al [27] showed that such large particles and urban aerosols enhance the convective intensity and affect cloud microphysics and charging processes, leading to lightning. The possible impacts of dust on cloud-drop (as well as ice nucleation) on simulated convective intensity will need to be investigated in a separate study using, for example, Spectral (bin) Microphysics (e.g., [27,33]).…”
Section: Aerosol Concentrationsmentioning
confidence: 99%